Active packaging coating based on Ocimum basilicum seed mucilage and probiotic Levilactobacillus brevis Lb13H: preparation, characterization, application and modeling the preservation of fresh strawberries fruit - Rahmati-Joneidabad, Mostafa; Alizadeh Behbahani, Behrooz; Taki, Morteza; Hesarinejad, Mohammad Ali; Toker, Omer Said (SPRINGER, 2025)
In this study, the probiotic Levilactobacillus brevis Lb13H was loaded to basil mucilage at concentrations of 0, 1.5 x 108 and 3 x 109 CFU/mL and used as an edible coating to increase the shelf-life of strawberries. At the end of the storage period (10 days at 4 degrees C), the sample coated with mucilage containing 3 x 109 CFU/mL of probiotic compared to the control sample, had lower pH and higher acidity, less soluble solids, lower fungal growth, the changes in less sensory parameters (color, odor, taste, texture, and overall acceptance) and firmer texture. Although the number of viable probiotic bacteria in the coating decreased during the storage period, at the end of storage time, the number of probiotic bacteria in both types of coating was higher than 6 log CFU/g. In addition, at the end of the storage period, the decay rate (72.40 vs. 26.30%), and weight loss (4.50 vs. 2.00%), ascorbic acid loss (27.53 vs. 36.86 g/kg), anthocyanin loss (225.10 vs. 253.54 g/kg) and total phenol loss (958.28 vs. 1310.19 g/kg) in the control sample was significantly higher compared to the sample containing 3 x 109 CFU/mL of probiotic. The study also employed Multilayer Perceptron (MLP) and Gaussian process regression (GPR) models to predict various variables related to the strawberries' quality, with GPR demonstrating higher accuracy in predictions compared to MLP. Mean Absolute Percentage Error (MAPE) indicator for GPR model was between 0.213% and 3.376% for all predicted variables. The results indicated that the coating with probiotics could enhance the shelf life of perishable fruits.
Keywords: Edible coating; Modeling; Artificial intelligence; Probiotic; Shelf life; LACTIC-ACID BACTERIA; EDIBLE COATINGS; SHELF-LIFE; POSTHARVEST QUALITY; ENERGY; FILMS; CONSUMPTION; SPOILAGE; NETWORK; FOOD; Food Science & Technology